Evaluation of selectively fertilized coconut hybrids (Cocos nucifera L.) for water use efficiency through stable isotope discrimination - Aisha Renju N A (Department of plant physiology, College of agriculture, 2015)
A study entitled “Evaluation of selectively fertilized coconut hybrids (Cocos nucifera L.) for water use efficiency through stable isotope discrimination” was undertaken with an objective to evaluate the selectively fertilized coconut hybrids for water use efficiency, and to study the mechanism of water stress tolerance in coconut, and to estimate genetic variability in coconut for water use efficiency through stable isotope discrimination. A pot culture experiment was conducted for three months in Rain out shelter of the Department of Plant Physiology, where one year old coconut seedlings of seven coconut varieties and hybrids (Kerasree, Keraganga, Malayan Yellow Dwarf, Gangabondam, West Coast Tall and selectively fertilized hybrids of Kerasree and Keraganga) were grown and evaluated for water use efficiency through gravimetric method. The experiment was laid out in CRD with equal sets of seedlings under two treatments viz 100 % Field Capacity (T1) and 50 % Field Capacity (T2) with 3 replications. Water transpired from individual seedlings were estimated daily through gravimetry. The transpiration loss was replenished by adding specific quantity of water to maintain the plants at respective soil moisture levels. Total dry matter accumulation was determined through the initial and final samplings. Physiological and biochemical analyses were done at monthly intervals. At the end of three months, leaf samples from experimental seedlings were collected and sent to Isotopic Ratio Mass Spectrophotometric (IRMS) facility, UAS Bangalore for stable isotope discrimination. Meanwhile, leaf samples from adult palms of 30 coconut genotypes were collected from RARS, Pilicode and sent for stable isotope discrimination. Among all genotypes, Kerasree S.F exhibited highest WUE (6.3 g/kg) under T2 by accumulating maximum dry matter (188.33 g) with a comparatively lower volume of cumulative transpired water. Results of carbon isotope discrimination was negatively correlated with gravimetric data of WUE so that genotype with highest water use efficiency (Kerasree S.F) marks the lowest discrimination value for C 13 (19.90). Decreased stomatal frequency and stomatal conductance up to 3 months in all coconut genotypes resulted in decreasing transpiration rate under 50 % F.C (T2). Relative water content was decreasing over the period of study under T2 for all varieties and highest tissue moisture content was maintained by Kerasree S.F (80.19 %). Wax deposition under water stress was highest in Kerasree (3.93 mg/cm2). Highest membrane integrity and chlorophyll stability index (99.19 %) under T2 was noticed in MYD. Pigment components viz chlorophyll a, chlorophyll b, total chlorophyll and carotenoids decreased with the extent of stress. Total soluble protein content decreased in all coconut types under T2. Proline content and activity of enzymatic antioxidants were high in selectively fertilized hybrid of Kerasree. Genetic variation for C13 discrimination was studied in 30 coconut genotypes that includes Talls, Dwarfs and Hybrids and the data revealed a discrimination range of (18.37-21.07). Among the coconut genotypes evaluated for WUE, hybrid Kerasree S.F was found to be the most water use efficient genotype under water deficit treatment, which coincides with its lowest value for C13 discrimination. Hence the study revealed that stable isotope discrimination can be used as an alternative for gravimetric method to screen out water use efficient genotypes. Moreover, efficacy of stress tolerance screening technique like selective fertilization is once again proved, which offers great prospects for drought tolerance breeding in perennials.